Communication Style of Project Manager's to Improve Project Performance [Study Case] on Resindo Group - Indah Nursanti, Indah; Umarela, Farid Hamid (International Journal of Social and Management Studies, 2023)
In the project management process in a mining consultant, a project that is carried out will certainly have a lot of processes and departments that intersect in it. It is undeniable, of course, that in the process of delivering information, of course, experiencing problems in distributing information due to the inability of a project manager to communicate existing information to be applied in communication and ongoing projects. Various types of communication styles of a project manager certainly combine intergenerational communication in a container in equating perceptions in order to achieve common goals. Because every generation has different expectations, communication styles and perspectives. However, the project manager is expected to be able to adopt a management strategy that is in accordance with the unique characteristics of each generation so as to enable employers to equalize perceptions and utilize the strengths of each of their workforce so that they can maximize their efforts to achieve the target of completing a project. This research was conducted to understand more deeply where the background of this research is that researchers want to understand the meaning of the communication strategy style of project managers in completing a given project. This research was conducted at the mining consulting company RESINDO group which was founded in 2009.